2021
DOI: 10.1111/1460-6984.12656
|View full text |Cite
|
Sign up to set email alerts
|

Shielding, hospital admission and mortality among 1216 people with total laryngectomy in the UK during the COVID‐19 pandemic: A cross‐sectional survey from the first national lockdown

Abstract: Background People with a total laryngectomy (PTL) rely on a permanent opening in their neck (stoma) to breathe. This altered anatomy may increase susceptibility to contracting and transmitting SARS‐CoV‐2. Aims To report on (1) the frequency and characteristics of PTL who tested positive for COVID‐19, (2) the receipt of advice regarding shielding and patient self‐reports of shielding, (3) hospital admissions and length of stay, and (4) mortality rates in this group durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…A study by Jayes et al ( 2022 ) described how UK Speech and language therapists (SLTs) supported differently abled individuals with communication disabilities to make decisions and participate in mental capacity assessments, best interest decision-making, and advance care planning during the COVID-19 pandemic. Govender et al ( 2021 ) investigated how people with a total laryngectomy (PTL) were impacted by COVID-19. Feldhege et al ( 2021 ) conducted an observational study on changes in language style and topics in an online Eating Disorder Community at the beginning of the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A study by Jayes et al ( 2022 ) described how UK Speech and language therapists (SLTs) supported differently abled individuals with communication disabilities to make decisions and participate in mental capacity assessments, best interest decision-making, and advance care planning during the COVID-19 pandemic. Govender et al ( 2021 ) investigated how people with a total laryngectomy (PTL) were impacted by COVID-19. Feldhege et al ( 2021 ) conducted an observational study on changes in language style and topics in an online Eating Disorder Community at the beginning of the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Representing a linguistic focus, another recent study by Heras-Pedrosa et al (2022) consisted of a systemic analysis of publications in health communication and COVID-19. It found that, in 2020, concepts related to mental health, mass communication, misinformation, and communication risk were more frequently used, and in the succeeding year (2021), vaccination, infodemic, risk perception, social distancing, and telemedicine were the most prevalent keywords.…”
Section: Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations